Shakespeare's Tragic Sequence. - Muir, Kenneth (Tragedies ;, 2013)
First published in 1972. The emphasis of this book is that each of Shakespeare's tragedies demanded its own individual form and that although certain themes run through most of the tragedies, nearly all critics refrain from the attempt to apply external rules to them. The plays are almost always concerned with one person; they end with the death of the hero; the suffering and calamity that befall him are exceptional; and the tragedies include the medieval idea of the reversal of fortune.